PENGARUH DEBT TO ASSET RATIO, DEBT TO EQUITY RATIO, TOTAL ASSET TURNOVER DAN CURRENT RATIO TERHADAP RETURN ON EQUITY PADA PERUSAHAAN SUB SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dian Ayu Andriani; Hilmiatus Sahla; Zulfa Khairina Batubara (Smart Education, 2022)
This research aims to determine the effect of Debt To Asset Ratio, Debt To Equity Ratio, Total Asset Turnover and Current Ratio on Return On Equity in Mining Sub-Sector Companies Listed on the Indonesia Stock Exchange. The research sample was 10 banking companies listed on the Indonesia Stock Exchange from 2015 to 2018. Data testing was carried out using the multiple linear regression analysis method. The results showed that partially the Debt to Asset Ratio variable had no effect on Return On Equity, seen from the results of the significant value 0.271 > 0.05 and the tcount (1.119) < ttable (2.02809), the Debt to Equity Ratio variable has no effect on Return On Equity seen from the results of the significant value 0.362> 0.05 and the value of tcount (0.924) < ttable (2.02809), the Total Asset variable Turnover has a significant effect on Return On Equity seen from the results of significant values 0.000 <0.05 and tcount (4.696) > ttable (2.02809), and the Current Ratio variable has no effect on Return On Equity seen from the results of the significant value of 0.455 > 0.05 and the value of tcount (0.755) < ttable (2.02809), Simultaneously that the value of sig. F of 0.000 < significant level of 0.05 (5%) and the value of Fcount (6.259) > Ftable (2.64).This means that it can be concluded that the variables Debt to Asset Ratio, Debt to Equity Ratio, Total Asset Turnover and Current Ratio have a significant effect on Return On Equity. Adjusted Rsquare value or coefficient of determination is 0.350. This result means that 35.0% of the variance or change in Return On Equity can be explained by variations of DAR, DER, TATO and CR while the rest (65.0%) is explained by other causes outside this research model.